2013
DOI: 10.1016/j.neuroscience.2013.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Irisin-immunoreactivity in neural and non-neural cells of the rodent

Abstract: Irisin is a recently identified myokine secreted from the muscle in response to exercise. In the rats and mice, immunohistochemical studies with an antiserum against irisin peptide fragment (42–112), revealed that irisin-immunoreactivity (irIRN) was detected in three types of cells; namely, skeletal muscle cells, cardiomyocytes, and Purkinje cells of the cerebellum. Tissue sections processed with irisin antiserum pre-absorbed with the irisin peptide(42–112) (1 μg/ml) showed no immunoreactivity. Cerebellar Purk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
139
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(148 citation statements)
references
References 25 publications
5
139
0
4
Order By: Relevance
“…Thus, it appears that time course changes of irisin concentrations in response to acute exercise are complex. Recent studies suggested that multiple sources (e.g., skeletal myocytes, adipocytes, cardiomyocytes and purkinje cells of cerebellum) for irisin production exist (Roca-Rivada et al 2013;Raschke and Eckel 2013;Dun et al 2013) and interactions with other cytokines and hormones (e.g., IL-6, BDNF, adiponectin) are involved (Pedersen and Febbraio 2012;Wrann et al 2013;Park et al 2013). These factors may explain, partially, the rapid reduction of irisin concentration immediately after LIE.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that time course changes of irisin concentrations in response to acute exercise are complex. Recent studies suggested that multiple sources (e.g., skeletal myocytes, adipocytes, cardiomyocytes and purkinje cells of cerebellum) for irisin production exist (Roca-Rivada et al 2013;Raschke and Eckel 2013;Dun et al 2013) and interactions with other cytokines and hormones (e.g., IL-6, BDNF, adiponectin) are involved (Pedersen and Febbraio 2012;Wrann et al 2013;Park et al 2013). These factors may explain, partially, the rapid reduction of irisin concentration immediately after LIE.…”
Section: Discussionmentioning
confidence: 99%
“…39 Roca-Rivada et al defined Irisin as the new adipokine with autocrine and endocrine activity, demonstrating that FNDC5/Irisin has a different pattern of secretion depending on adipose tissue type. 39 Besides skeletal muscle and adipose tissue, it has been shown that Irisin might have a role in the central nervous system, as demonstrated by studies that revealed that rat and mice cerebellar Purkinje cells expressed FNDC5, 40 which is also required for the adequate neural differentiation of mouse embryonic stem cells 41 and regulates hippocampal neurogenesis in a dose-dependent manner. 42 The key role of Irisin in neuronal differentiation and function gains particular relevance for neurodegenerative diseases, such as Alzheimer and Parkinson, and it may represent the molecular explanation for the positive correlation between physical activity and healthy brain.…”
Section: Irisin Synthesis Beyond the Muscle And Its Autocrine Actionmentioning
confidence: 99%
“…In particular it was reported the secretion of irisin mainly by subcutaneous adipocytes in rats and humans depending on exercise and nutritional status [20]. In addition, it was found that irisin is expressed in glutamate decarboxylase-positive Purkinje cells of the cerebellum in the brain [21], and an important role in the neurogenic regulation was suggested [22,23]. Interestingly, it appears to have no in vitro effect on cell proliferation and malignant potential of obesityrelated cancer cell lines in physiological and higher physiological/pharmacological concentrations [24].…”
Section: Introductionmentioning
confidence: 99%